Rapid identification and determination of pyrrolizidine alkaloids in herbal and food samples via direct analysis in real-time mass spectrometry. (1st January 2021) - Chen, Yilin; Li, Linnan; Xiong, Fen; Xie, Yanqiao; Xiong, Aizhen; Wang, Zhengtao; Yang, Li
Highlights: An efficient DART-MS analysis for toxic PAs in complex matrices is firstly developed. Rapid identification and determination of PAs in herbal medicines, preparations and foods are presented. The obtained results are in good agreement with conventional HPLC-MS method. DART-MS provides a facile fashion for safety assessment of PAs-containing herbal and food products. Abstract: Pyrrolizidine alkaloids (PAs) are naturally occurring plant toxins associated with severe liver damage if excessive ingestion. Herein, a novel analytical strategy on utilizing direct analysis in real-time mass spectrometry (DART-MS) was developed, and applied in analysis of six representative PAs. The calibration curves in the range of 10–1000 ng·mL −1 were established, and relative standard deviations (RSDs) were less than 10%. The limits of detection (LODs) and limits of quantitation (LOQs) were 0.55–0.85 ng·mL −1 and 1.83–2.82 ng·mL −1, respectively. The feasibility of method was indicated by analysing real samples including Gynura japonica, drug tablets, granules, and fresh cow's milk. Moreover, the results of DART-MS were in good agreement with those observed by high performance liquid chromatography mass spectrometry (HPLC-MS), but consumed less time without chromatographic separation. This research provides a facile fashion for safety assessment of herbal and food products containing PAs and presents promising applications in food, pharmaceutical and clinical analysis.